Differential Effects of G- and F-Actin on the Plasma Membrane Calcium Pump Activity - Vanagas, Laura (2012)
We have previously shown that plasma membrane calcium ATPase (PMCA) pump activity is affected by the membrane protein concentration (Vanagas et al., Biochim Biophys Acta 1768:1641-1644, 2007). The results of this study provided evidence for the involvement of the actin cytoskeleton. In this study, we explored the relationship between the polymerization state of actin and its effects on purified PMCA activity. Our results show that PMCA associates with the actin cytoskeleton and this interaction causes a modulation of the catalytic activity involving the phosphorylated intermediate of the pump. The state of actin polymerization determines whether it acts as an activator or an inhibitor of the pump: G-actin and/or short oligomers activate the pump, while F-actin inhibits it. The effects of actin on PMCA are the consequence of direct interaction as demonstrated by immunoblotting and cosedimentation experiments. Taken together, these findings suggest that interactions with actin play a dynamic role in the regulation of PMCA-mediated Ca2+ extrusion through the membrane. Our results provide further evidence of the activation-inhibition phenomenon as a property of many cytoskeleton-associated membrane proteins where the cytoskeleton is no longer restricted to a mechanical function but is dynamically involved in modulating the activity of integral proteins with which it interacts. © 2012 Springer Science+Business Media New York.